Assessment of Environmental Management in Lake Toba, Samosir Regency, North Sumatera Province, Indonesia - M Sianturi, Novdin; Khairul Amri Kamarudin, Mohd; Ekhwan Toriman, Mohd; Abd Wahab, Noorjima; Hakparn, Surachate; Lertbunchardwong, Kanittha; Potikengrith, Tepvisit; Sujaul Islam, Mir; Harith, Hazamri; ., . (International Journal of Engineering and Technology, 2018)
Earth, water and other natural resources are controlled by government and used totally for society’s prosperity. If the problem cannot be anticipated, it will cause conflicts in society by personal or certain group interest when the demand is no longer equal with the supply of water resources. The aim of the study is to examine the Environmental Management in Lake Toba through water quality and waste management system. From 2013 until 2017 showed the increasing of waste management with a sorting method in the polling stations based on services zone priority and the coverage of existing garbage service improve the average to 1.673 %, coverage of existing TPS services an average of 2.07 %, and the scope of service of garbage transport trucks, Garbage Container and Bike Rickshaw average 12.03 %. The value of the investment Cash flow, Net worth by 2020 NPV at 15% interest rate positive value of Rp 2,043,325,165, an IRR of 9.664 % > MARR of 15%, a B/C ratio of 1.13 > 1 and PP 4.4 years (4 years 4 months 11 days), shorter than the 10-year investment period.